Second occupation – reoccupation - Jakubčionis, Algirdas (Genocidas ir rezistencija, 2001)
The historical terms and historical periodisation of Lithuania’s recent history are highly interrelated. This paper analyses how the Lithuanian historiography in its different schools (the diaspora, independent Lithuania) distinguishes between different moments of the Soviet occupation, how such periodisation is justified, and how interpretations have changed.